Dynamic Frequency Allocation in SLICE Considering both BER and Distance - Lei Wang; Min Zhang; Hui Ding; Lifang Zhang; Shanguo Huang; Xin Chen (Institute of Advanced Engineering and Science, 2012)
Proposed in this paper is a dynamic resource-aware routing and frequency slots allocation scheme with consideration of both BER requirement and distance adaptive modulation (RA-BERR-DA) for spectrum-sliced elastic optical path networks (SLICE).Numerical simulations are conducted to analysis network performance such as blocking rate and the number of used frequency slots. The results demonstrate that this scheme is able to decrease traffic blocking and improve resource utilization in dynamic spectrum assignment. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1448